Controlling water-mediated interactions by designing self-assembled monolayer coatings - Hsieh Chen (Nature Portfolio, 2021)
Abstract Engineered nanoparticles have been broadly used in biological and geological systems. Hydrophilic molecules such as polyols have been used as coatings on nanoparticle surfaces due to their good biocompatibility and solubility in saline water. However, polyol coatings can cause huge retention of nanoparticles when encountering mineral surfaces. Here, molecular dynamics simulations enlightened that the strong adhesion of hydrophilic coatings to mineral surfaces stemming from the partitioning of the hydroxy groups on the hydrophilic molecules to the well-defined bound hydration layers on the mineral surfaces. To mitigate the nanoparticle adhesion, we investigated introducing small percentages of omniphobic fluoroalkanes to form a bicomponent system of hydrophilic and fluoroalkanes, which greatly perturbed the hydration layers on mineral surfaces and resulted in nonstick surface coatings. Our results provide important insight for the design of tunable “stickiness” nanoparticle coatings in different mineralogies, such as applications in subsurface environments or targeted delivery in mineralized tissues.